2021
DOI: 10.1002/jor.25120
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors 3‐months after anterior cruciate ligament reconstruction predict 6‐month subjective and objective knee outcomes

Abstract: The objective of the study was to determine if psychological readiness for sport and knee self-efficacy assessed early (3 months) after anterior cruciate ligament reconstruction (ACLR) are predictive of self-reported functional outcomes, quadriceps strength, and knee mechanics while running at the time of return to sport training (6 months). Thirty athletes with unilateral ACLR completed the ACL Return to Sport after Injury (ACL-RSI) and Knee Self-Efficacy Scale (K-SES) 3 months after ACLR and completed self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…33,51 Chmielewski and George 9 concluded that psychosocial correlates that predict outcomes - such as the subfactors as well as larger themes of kinesiophobia, self-efficacy, and pain catastrophizing - can be detected as early as 4 weeks after ACLR. Erickson et al 12 observed correlates of psychosocial measures at 3 months post-ACLR to predict 6-month outcomes. Both suggested that earlier detection creates opportunities to intervene and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33,51 Chmielewski and George 9 concluded that psychosocial correlates that predict outcomes - such as the subfactors as well as larger themes of kinesiophobia, self-efficacy, and pain catastrophizing - can be detected as early as 4 weeks after ACLR. Erickson et al 12 observed correlates of psychosocial measures at 3 months post-ACLR to predict 6-month outcomes. Both suggested that earlier detection creates opportunities to intervene and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is needed to identify the optimal timeframe for psychosocial testing, but current consensus supports earlier testing. 12 Earlier detection may help clinicians implement interventions; however, evidence-based research is still needed to determine standardized interventions. Ultimately, the inconsistencies and failure to evaluate the psychosocial profile of patients may impact outcomes negatively after ACLR.…”
Section: Measuring Psychosocial Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because injuries are bound to happen in this physically active population, tactics to promote successful recovery and prevent subsequent injuries are needed to save time and resources spent on rehabilitation. Many studies have examined the associations of psychologic variables and return to physical activity with the risk of reinjury in the context of sports injuries [7,12,19,27,32,44]. Such findings are encouraging, because soldiers are tactical athletes who experience injuries because of physical activity similar to that of civilian athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previously identified injury risk factors such as age [8,18,33,47], gender [4,38], and prior injury [9,44,51], which are nonmodifiable [39], psychologic variables have been known to fluctuate across different stages of the health injury continuum [48], similar to physical function, and could be future targets of intervention to aid in successful return to full duty. There is no universal consensus on the defintion of "psychologic readiness" to return to sports [32]; however, relationships between several different psychologic constructs and return to sport [27], future injury [44], rehabilitation adherence [12], and functional outcomes [7] after injuries have been reported. For instance, fear of reinjury has been associated with poor rehabilitation outcomes, difficulties with returning to sport, or even with function and distraction when returning to sport [19].…”
Section: Introductionmentioning
confidence: 99%